Dark and bright empathy: phenomenological and anthropological reflections - Throop, C; Zahavi, D (University of Chicago Press, 2020)
The aim of our contribution is to clarify the nature of empathy and its role in sociality. Taking issue with a recent proposal by Bubandt and Willerslev, we argue that their conceptualization and definition of empathy is confused, that they fail to distinguish sufficiently clearly between empathy and other forms of social cognition, and that their main claim, that empathy has a dark side to it, and can be used for nefarious purposes, far from being novel, was already recognized by leading empathy theorists at the beginning of the 20th century. We then revisit and present core ideas from formative writings on empathy found in early phenomenology, we demonstrate the anthropological relevance of these ideas, and argue that phenomenologists such as Husserl, Stein and Scheler develop an account of the link between empathy, alterity and sociality that is considerably more refined and sophisticated than anything offered by Bubandt and Willerslev. In the final part of the paper, we engage with Geertz’ highly influential claim that anthropologists can safely leave empathy behind and argue that empathy plays such a fundamental role in the fabric of social life that its use in ethnographic research is not only permissible, but unavoidable.